THE INTRODUCTION OF TECHNOLOGY FOR THE PRODUCTION OF A NEW TYPE OF SHIRT SILK CREPE FABRIC AT DOMESTIC ENTERPRISES - Mukhamadrasulov Shamsiddin Khasanovich; Dildora Yuldasheva (American Journals Publishing, 2023)
In this paper, a newly created type of "Crepe Fabric" is studied, which has a new structure, combines the properties of yarns and the structure of the fabric, and provides the fabric with increased crepe properties. It also discussed the introduction to production at "YODGORLIK" LLC, as well as the prospects of increasing their type and increasing the export potential of the industry.At a time when the demand for products made from natural raw materials is increasing day by day, it is important to increase the volume of silk fabrics in world fashion, to find ways to create a new assortment of silk fabrics. Our government has put a lot of urgent issues before textile experts and scientists. Using existing opportunities, expanding the volume of production of high-quality fabrics from natural fibres, and solving the problems of achieving trade with competitive products under the label "Made in Uzbekistan" on the world market are some of the main urgent problems that are waiting for a solution today.
Keywords: Raw silk, silk thread, mating, blown silk, crepe fabric, steaming, rewinding, carding, weaving, finishing.